Exploring the Effect of Hybrid Work and Onsite Work on Employee Motivation in Thailand - Sermcharoenkit, Pakwan; Thanasrivanitchai, Jul (Rajapark Journal, 2025)
This study examined 1) differences in motivation levels between employees utilizing onsite work and those utilizing hybrid work arrangements, 2) the effect of a dedicated workspace on hybrid employee motivation, and 3) the effect of marital status on employee motivation. The sample comprised 400 Thai employees aged 20–60 years, consisting of 200 onsite and 200 hybrid employees. Participants were selected using Cochran’s formula for finite populations. Data were collected via an online questionnaire adapted from the multidimensional work motivation scale, focusing on four types of motivation: extrinsic regulation (social), extrinsic regulation (material), and intrinsic motivation. Statistical analyses included descriptive statistics, t-tests, ANOVA, and MANOVA. The results revealed three key findings: 1) Work conditions (onsite vs. hybrid) did not have a statistically significant impact on any of the motivation types (p > 0.05). 2) Among hybrid employees, having a dedicated workspace significantly increased extrinsic regulation (social) and extrinsic regulation (material) motivation. 3) Marital status differentially affected motivation: single hybrid employees reported higher extrinsic regulation (social) than married employees in either work condition, and higher extrinsic regulation (material) than married hybrid employees. These findings underscore the importance of providing equal opportunities irrespective of work conditions, establishing dedicated workspaces for hybrid employees, and accounting for personal circumstances when managing motivation across diverse employee groups.